Digital image watermarking based on fractal transform - Ni, Zhicheng. (2008)
This thesis presents a digital image watermarking algorithm based on the fractual transform. This algorithm can successfully resist the geometric attacks on the watermarked image. This algorithm can be used on both color and gray images and it does not need the original image in the stage of watermark extraction.